A critical and experimental study of the serial painting method in child therapy - Haffner, Christopher (The University of Edinburgh, 1951)
It is generally assumed by psychologists that childrens drawings and paintings can be an aid to the study of personality. I+,Iore recently these are being used as an adjunct to various therapeutic techniques. But the rationale for their employment as a diagnostic and therapeutic aid is,at the present time,largely based on a worker's orientation and inclinations and,as a part of psychotherapy they often become a tool which may be manipulated by the therapist to serve interpretations.

In comparison with their large scale application in practice the number of fundamental and empirical investigations in this field has been small and no systematic studies about the total significance of graphic methods in children with emotional disorders exist. This fact led me to think that an empirical investigation on experimental lines in conjunction with therapeutic work could help in providing more than intuitive clues to the manner in which serial graphic productions fulfil a function in therapeutic methodology.'The research, on the lines put forward by me,was approved by the Board of Electors of Guy's Hospital as being suitable for the work of the Sir Alfred Fripp Memorial Fellowship in Child Psychology, which I held from June 1947 until December 1949.

Basic Aspects. The research contained in this thesis is presented in three sections.These sections represent the actual stages through which it has evolved during the period of three years.

1.A study of the foundations upon which further progress in this field is to be built,and the definitions of aims. 2.The application of serial graphic methods to individual case study. 3.The comparative examination of certain painting trends in a therapeutic group of children.

Accordingly section I.gives a critical survey of some of the more important work in the field of development and in those aspects of personality study which have a direct bearing on the method developed for this investigation. Section II.contains a detailed account of the practical application of this method from the clinical standpoint in a boy aged 6 who suffered from asthma.Iere the main emphasis has been placed on trends in form-expression.Spontaneous verbal associations,given at various intervals in response to serial productions,formed an integral part in the method of eliciting the child's attitudes to these expressive trends. A series of 28 consecutive microfilms in colour is presented with this case report.

Section III. gives an account of the group as a whole and postulates criteria for assessment of "primary graphic trends ". These are concerned with kinesthetic elements in painting and attitudes to space,colour and form.These criteria were initially developed from empirical study of a large number of paintings. Variants to graphic trends were studied by means of an analysis in each child of 25 consecutive productions painted during the interval of one year.The products were assessed with the help of a four point scale.By means of this a much more accurate impression of the total material as well as of the individual(r contained therein could be gained than through empirical examination alone.Finally the relationship between certain extreme tendencies shown and the type of disturbance from which the child suffered was examined.The various subsections contain illustrative case material.

The therapeutic group on which these observations are based consists of 40 children who suffered from a variety of emotional disorders and somatic dysfunctions.In some of these cases treatment and follow -up extended over a period of 4 years. Selection was determined by age limitation,preference for painting,a preliminary period of observation,exclusion of children with defective or "dull "intelligence,and absence of prolonged spontaneous remissions of somatic symptoms. Graphic material sent with the "appendix" to this thesis contains a further selection of colour micro -photographs from many different children and a variety of original productions.Table III.on page 154 contains reference numbers for trait descriptions and illustrations in the appendix. All this material is the property of the Department of Psychological Medicine,Guy's Hospital,London S.E.l.

Conclusions. Very generally speaking these may be divided into two parts, 1.General conclusions about the clinical validity of graphic methods in child therapy.

2.Specific findings about the differentiating value of graphic _fora and spontaneous verbal associations. 1.) Serial methods in child therapy offer distinct possibilities for diagnosis,treatrnent and prognosis with children who show a preference for colour- media.(See p.23.)The meaning behind the surface aspects of childrens' art work is more difficult and complex than many recent studies lead us to believe.T'his applies in particular tt interpretive approaches.The evaluation of childrens' art work requires experience from the therapist or investigator.

2.)The question of specificity of formal traits and associated verbal responses in the non -psychotic child is an interesting one.Consistent traits are frequently seen in the serial patterning over periods of time.Their value as indicators would depend on our ability to isolate three main groups of components from any individual series, a.those that are relatively consistent with maturation, b.those that are based on innate factors of the individual constitution, c.those that are an expression of temporary emotional conflicts.